2015
DOI: 10.1177/0267659115589622
|View full text |Cite
|
Sign up to set email alerts
|

Novel use of the AngioVac® system to remove thrombus during simultaneous extracorporeal membrane oxygenation life support

Abstract: Extracorporeal membrane oxygenation (ECMO) was introduced to clinical medicine over 40 years ago. While initially used as a treatment for acute respiratory failure in infants, the use of ECMO has grown to include respiratory and circulatory failure in both children and adults, cardiogenic shock, pulmonary embolism, sepsis, trauma, malignancy, pulmonary hemorrhage and as a treatment for hypothermic drowning.(1) Recent technological improvements in ECMO circuitry make it possible to minimize anticoagulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…2 In one case, the AngioVac device was used to evacuate thrombus associated with the venous cannula of an extracorporeal membrane oxygenation (ECMO) circuit, again with success. 3 The complete success rate, defined as removal of all thrombus, was 75% (n = 43), with an 11% (n = 6) partial success rate. In 14% (n = 8) of cases, minimal or no thrombus was retrieved.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…2 In one case, the AngioVac device was used to evacuate thrombus associated with the venous cannula of an extracorporeal membrane oxygenation (ECMO) circuit, again with success. 3 The complete success rate, defined as removal of all thrombus, was 75% (n = 43), with an 11% (n = 6) partial success rate. In 14% (n = 8) of cases, minimal or no thrombus was retrieved.…”
Section: Resultsmentioning
confidence: 98%
“…In cases of catheter-related thrombus in patients with right to left shunts, as with a Fontan shunt, the AngioVac may be used prophylactically during catheter removal to prevent paradoxical PE. 3 Similarly, in the setting of inferior vena cava tumor thrombus, the AngioVac device may be used to prevent iatrogenic PE during surgical thrombectomy. 5 The AngioVac device can be used for thrombectomy of an ECMO cannula while maintaining ECMO flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of 53 retrieved searched articles, 42 met our inclusion criteria. The PRISMA flowchart is shown in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…At present, there is no report on the application of vascular interventional therapy. However, it has been reported that the AngioVac System can successfully evacuate the thrombus in cases of ECMO-related thrombosis [19].…”
Section: Discussionmentioning
confidence: 99%